The impact of foremen’s paternalistic leadership on construction workers’ safety behaviors: considering the effects of team safety climate, workers’ psychological safety and power distance - Wang, Lixia; Luo, Xun; Li, Hujun; Chen, Huihua (Frontiers in Public Health, 2025)
This study investigates how foremen’s paternalistic leadership (FPL) influences construction workers’ safety behaviors (WSB) in China, and how team-level and individual-level psychological mechanisms shape this relationship. Drawing on leader–member exchange theory, psychological safety theory, and cultural congruence perspectives, this research proposes a dual-mediation model involving team safety climate (TSC) and workers’ psychological safety (WPS), with power distance (PD) as a moderating variable. A cross-sectional survey was conducted with 263 frontline workers across three Chinese cities. Structural equation modeling revealed that FPL significantly enhanced WSB both directly (β = 0.104, p < 0.001) and indirectly through TSC (indirect effect = 0.195) and WPS (indirect effect = 0.204). Multiple regression analysis showed that PD moderated the impact of FPL on both mediators, with stronger associations observed among high-PD individuals. These findings contribute to safety leadership research by contextualizing paternalistic leadership within construction settings. The results also highlight culturally contingent pathways through which leadership affects safety outcomes, offering theoretical insights and practical implications for improving construction site management and training.